Towards a harmonised Total Diet Study approach: a guidance document - European Food Safety Authority (Wiley, 2011)
Abstract A Total Diet Study (TDS) can be a complementary approach to traditional monitoring and surveillance programs, which instead of focusing on compliance is designed to provide a solid basis for calculating population dietary exposure and assessing potential impact on public health. A TDS includes the selection of foods based on food consumption data to represent a large portion of a typical diet, their preparation to food as consumed and the subsequent pooling of related foods before analysis. There is already a wealth of international TDS data available, but to better enable comparisons it is important that methods are harmonised to the extent possible. The Working Group of experts provides a definition of the TDS approach highlighting its inherent value; it gives guidance for a harmonised methodology starting from the TDS planning to the collection of analytical results, exposure assessment calculation and communication of TDS results; and it proposes a general approach to facilitate the use of TDS information at international level. A TDS can be used for screening purposes or as a more refined exposure assessment tool. It provides background concentration and exposure levels of chemical substances in a range of representative foods prepared for consumption, while monitoring and surveillance programs can better capture highly contaminated individual food items. Their complementarities would allow the identification of the relative importance of individual sources of chemical substances from the whole diet. In conclusion, a TDS is considered to be a good complement to existing food monitoring or surveillance programs to estimate population dietary exposure to beneficial and harmful chemical substances across the entire diet. Harmonising the TDS methodology will enhance the value of these programs by improving the comparability at international level.